Eventos legais e sua descrição conforme a semântica de frames - Minghelli, Thaís Domênica (Universidade do Vale do Rio dos Sinos, 2016)
According to the demand for increasingly efficient computer systems with respect to information retrieval, as well as the large number of legal sites, ontologies have proved to be useful means of organizing information in computer systems. Facing this scenario, it is believed that the study about the theme of events and the proposition of a semantic description of the legal civil lawsuit can collaborate for the representation of knowledge, for that be theoretically well founded, reflecting later in more effective computing systems regarding the organization of information and its retrieval. In this sense, this dissertation aims to highlight that the events linked to the civil lawsuit, concerning the ontological category Legal Events, can be described according to Frame Semantics. Meaning that an approach that gives account of the representation of successive situations, of participants who play different roles, as well as involves relations. To address this approach, first of all the conception of event is examined in accordance to three different optics, the linguistic, the ontological and the legal. Reflected in these biases, it is examined the notion of role, until, at last, it is moved to the main theory, analyzing to what extent the main precepts of the semantic theory of frames and its computational counterpart FrameNet are needed for the description of the civil procedural domain, with the guidance of the scope of this work, which is to describe the ontological category Legal Events through the notion of frame. In the empirical stage, it is meant with the data to ratify what the theoretical study indicated, having the results shown that the events linked to the civil lawsuit case can be described as Frame Semantics, as well as the notions of frame, frame elements, and the relations between frames, which consist of necessary conceptions for the description of the ontological category Legal Events.
Keywords: Semântica de frames; Processo civil; Eventos legais; Papéis; Relações; Frame semantics; Civil law; Legal events; Roles; Relations; ACCNPQ::Lingüística, Letras e Artes::Lingüística